2014
DOI: 10.2134/jeq2013.07.0284
|View full text |Cite
|
Sign up to set email alerts
|

Chloride Dispersion across Silt Deposits in a Glaciated Bedrock River Valley

Abstract: Soil and groundwater from the Neponset River floodplain deposit that receive high concentrations of deicing agents from nearby highways were investigated. The silty sand floodplain is separated by a silty aquitard from the underlying aquifer that serves as a public water supply. We made a transport-based assessment of the capacity of the aquitard to protect the underlying aquifer. One hundred seventeen soil samples and 469 groundwater samples collected during a period of 4 yr from boreholes and 10 wells groupe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…As a consequence, natural attenuation of the contaminant plume through volatilization and subsequent release into the atmosphere is a rather slow process. The above conclusion is expected to be valid in most subsurface conditions since the vertical dispersivity of 0.05 m assumed in this study is already a relatively high value in natural aquifers (Rotaru et al, 2014). molar fractions in both liquid and gas phases.…”
Section: Tce Transport Without Thermal Energy Storagesupporting
confidence: 60%
“…As a consequence, natural attenuation of the contaminant plume through volatilization and subsequent release into the atmosphere is a rather slow process. The above conclusion is expected to be valid in most subsurface conditions since the vertical dispersivity of 0.05 m assumed in this study is already a relatively high value in natural aquifers (Rotaru et al, 2014). molar fractions in both liquid and gas phases.…”
Section: Tce Transport Without Thermal Energy Storagesupporting
confidence: 60%
“…Vertical dispersivity (z) 0.005 m f) a) Ratio of molar masses: Y VC-DCE = (62.5 g/mol) / (96.4 g/mol) b) Assessed from soil and water concentrations found from site descriptions in Jørgensen et al (2007a;2007b) c) Assumed to be the same as I d) Assessed from site descriptions in Jørgensen et al (2007a;2007b) e) Assessed from site description in Jørgensen et al (2007a;2007b) using Darcy's Law f) Chosen from an interval found from a literature review (Chiang et al, 1989;Mallants et al, 2000;Rivett et al, 1994;Robertson et al, 1991;Rotaru et al, 2014;Schulze-Makuch, 2005). Intervals are: α L 0,2-1 m, α T 0,0025-0,3 m, and α V 0,008-0,01 m. Figure 7a shows the vertical model results and the observed concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…Less attention has been given to the degradation of nitrobenzene at low temperature. In nature, most soil and groundwater temperatures are around 10 to 12 8C, with the annual change , 0.1 8C (Wang et al, 2005;Rotaru et al, 2014;Kurylyk et al, 2013;Gunawardhana and Kazama, 2011;Wang et al, 2014). This temperature is inhibitory to the growth and metabolism of most microorganisms; this, in turn, greatly compromises their ability to degrade organic matter (Nemecek-Marshall et al, 1993;Lu et al, 2010;Wu et al, 2006;Cindy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%